Fractal basins of escape and the formation of spiral arms in a galactic potential with a bar - Ernst, Andreas; Peters, Thomas (Monthly notices of the Royal Astronomical Society, 2014)
ABSTRACT. We investigate the dynamics in the close vicinity of and within the critical area in a 2D effective galactic potential with a bar of Zotos. We have c
Gesehen am 07.08.2020